Phacoemulsification: Complications in First 300 Cases - Tahir Ahmed, Abrar Ali, Tabassum Ahmed (Pakistan Journal of Ophthalmology, 2007)
Purpose: To find out complications of phacoemulsification in our first 300 cases. Material and Methods: Retrospective analysis of our first 300 cases of phacoemulsification was done. Operations were performed in different hospitals of city. After thorough examination and investigations, patients were operated. Most were operated under retrobulbar anaesthesia. First examination was on first post operative day and then followed up after one week, three weeks and eight weeks. Their operative and postoperative complications were analysed. Results: Posterior capsular rupture was the most common intraoperative complication in our initial cases. Corneal edema on first postoperative day was significant problem and because of this vision on first post operative day was low in most of our initial cases. After three weeks the vision was 6/12 or better in 83% of cases. Conclusion: Complications rate in initial learning curve was higher, which was dissatisfying for both surgeon and patients. Better outcome was achieved with more experience and adopting better techniques.